A Historical Analysis of The Padovan Sequence - Renata Passos Machado Vieira; Francisco Regis Vieira Alves; Paula Maria Machado Cruz Catarino (International Journal of Trends in Mathematics Education Research, 2020)
In the present text, we present some possibilities to formalize the mathematical content and a historical context, referring to a numerical sequence of linear and recurrent form, known as Sequence of Padovan or Cordonnier. Throughout the text some definitions are discussed, the matrix approach and the relation of this sequence with the plastic number. The explicit exploration of the possible paths used to formalize the explored mathematical subject, comes with an epistemological character, still conserving the exploratory intention of these numbers and always taking care of the mathematical rigor approached